2015
DOI: 10.18632/oncotarget.6409
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib synergizes with poly(ADP-ribose) glycohydrolase inhibitors to induce cell death in AML cells via a BTK-independent mechanism

Abstract: Targeting Bruton's tyrosine kinase (BTK) with the small molecule BTK inhibitor ibrutinib has significantly improved patient outcomes in several B-cell malignancies, with minimal toxicity. Given the reported expression and constitutive activation of BTK in acute myeloid leukemia (AML) cells, there has been recent interest in investigating the anti-AML activity of ibrutinib. We noted that ibrutinib had limited single-agent toxicity in a panel of AML cell lines and primary AML samples, and therefore sought to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Our present study shows that a subset of patients has chemokine-responsive AML cells, and similar dual-targeting may be possible in AML. This hypothesis is supported by recent studies; ibrutinib has direct antileukemic effects in human AML ( 40 ) and is in addition able to alter chemokine-dependent AML cell migration ( 41 ). Our present studies therefore suggest combined targeting of AML cell survival, and migration (i.e., chemokine targeting) should be considered for patients with chemokine-responsive AML cells.…”
Section: Discussionmentioning
confidence: 52%
“…Our present study shows that a subset of patients has chemokine-responsive AML cells, and similar dual-targeting may be possible in AML. This hypothesis is supported by recent studies; ibrutinib has direct antileukemic effects in human AML ( 40 ) and is in addition able to alter chemokine-dependent AML cell migration ( 41 ). Our present studies therefore suggest combined targeting of AML cell survival, and migration (i.e., chemokine targeting) should be considered for patients with chemokine-responsive AML cells.…”
Section: Discussionmentioning
confidence: 52%
“…Suggested mechanism: increased intracellular ROS production in cells treated with combination. [ 256 ] ND-2158 (IRAK4 inhibitor) ABC-DLBCL - ABC-DLBCL cell lines OCI-Ly10 and TMD8 - OCI-Ly10 xenografts MYD88-IRAK4 signaling is important for ABC- DLBCL viability Combination was more effective than ND-2158 alone in inhibiting IKK activity, enhancing apoptosis, and blocking tumor growth in mice. [ 257 ] PU-H71 (Binds to tumor enhanced HSP90 complexes) ABC-DLBCL DLBCL cell lines (HBL-1 and TMD8) teHSP90 complexes are associated with tumor survival.…”
Section: Ibrutinib In Combination Therapies and Second Generation Btkmentioning
confidence: 99%
“…Recently, one study indicated that ibrutinib combined with ethacridine had a synergistic cytotoxicity to AML cells [24]. Interestingly, Pillinger et al and Wu et al found ibrutinib was particularly effective in inhibiting FLT3-ITD mutant AML cell survival [25, 26].…”
Section: Introductionmentioning
confidence: 99%